Shape of the dilated aorta in children with bicuspid aortic valve - Christopher R Mart; Bryn E McNerny (Wolters Kluwer Medknow Publications, 2013)
Background: The dilated aorta in adults with bicuspid aortic valve has been shown to have different shapes, but it is not known if this occurs in children. This observational study was performed to determine if there are different shapes of the dilated aorta in children with bicuspid aortic valve and their association with age, gender, hemodynamic alterations, and degree of aortic enlargement. Methods: One hundred and eighty-seven echocardiograms done on pediatric patients (0 - 18 years) for bicuspid aortic valve, during 2008, were reviewed. Aortic valve morphology, shape/size of the aorta, and pertinent hemodynamic alterations were documented. Aortic dilation was felt to be present when at least one aortic segment had a z-score > 2.0; global aortic enlargement was determined by summing the aortic segment z-scores. The aortic shape was assessed by age, gender, valve morphology, and hemodynamic alterations. Results: Aortic dilation was present in 104/187 patients. The aorta had six different shapes designated from S1 through S6. There was no association between the aortic shape and gender, aortic valve morphology, or hemodynamic abnormalities. S3 was the most common after the age of six years and was associated with the most significant degree of global aortic enlargement. Conclusions: The shape of the dilated aorta in children with bicuspid aortic valve does not occur in a uniform manner and multiple shapes are seen. S2 and S3 are most commonly seen. As aortic dilation becomes more significant, a single shape (S3) becomes the dominant pattern.